Von Willebrand factor and hematogenous cancer metastasis under flow - Xu, Wenxuan; Tan, Xi; Li, Morgan L.; Xu, Hanzhi; Villegas, Jasmine; Fu, Hongxia (Frontiers in Cell and Developmental Biology, 2024)
Hematogenous metastasis involves cancer cell migration to different locations from the primary tumor through the blood circulation. Von Willebrand factor (VWF) has been shown to play an important role in circulating tumor cell adhesion to and extravasation from the endothelial cell lining of blood vessel walls during cancer metastasis. VWF may contribute to this process by interacting with tumor cells, endothelial cells and platelets through various cell membrane receptors, such as platelet glycoprotein (GP)Ibα, P-selectin, ανβ3 and αIIbβ3 integrins, and glycocalyx. Blood flow can mechanically extend and activate VWF to bind platelets and associate intermolecularly with other VWF molecules in plasma or on the surface of endothelial cells, cancer cells, or platelets. This suggests a mechanoregulatory role of VWF in mediating the interactions between VWF and these cells to promote cancer cell adhesion to blood vessels. In this review, we will summarize the current knowledge of VWF function and the role of hydrodynamic forces in hematogenous cancer metastasis.